Gender and education: the vision and activism of Rokeya Sakhawat Hossain - Quayum, Mohammad Abdul (2014)
Rokeya Sakhawat Hossain (1880-1932) was a pioneering feminist writer, educationist and activist in colonial Bengal, who not only sought to emancipate women from the deeply entrenched values of Indian social and cultural patriarchy through her darkly satirical and provocative writings, but also actively pursued her idea of empowering women through education by setting up a school for Muslim girls. This paper will investigate Rokeya’s feminist ideology and her educational programmes undertaken for the betterment of Indian women, especially Bengali Muslim women. I intend to argue that although born into an orthodox family and brought up in strict purdah without any formal education, Rokeya had that rare foresight and courage to challenge the social status quo of her time and ridicule many of the outmoded gender practices in her writings, and even turn gender relations upside down by creating a Ladyland in her utopian narrative Sultana’s Dream (1905), in which men are confined to indoors while women run the state. Moreover, she was practical enough to reify her vision by taking steps to eradicate women’s ignorance and invigorate their sense of self, by setting up a school in Calcutta and by running programmes to educate slum women through the association for Muslim women, Anjuman-i-Khwateen-i-Islam, which she founded in 1916 – all at a time when Indian Muslim women were expected to live in confinement in the zenana, and any attempt to educate them was seen as blasphemous.